PERAN DAN KEWENANGAN OTORITAS JASA KEUANGAN (OJK) TERHADAP KEAMANAN TRANSAKSI DI PASAR MODAL - Elvira Fitriyani Pakpahan; Eric Kurniawan; Kelfin Candra; Silvi Yanti (Prodi Ilmu Hukum, Universitas Teuku Umar, 2020)
The word